Numerical simulations of solid suspensions in a gravity thickener - Mahmoud Alzoubi; Antoine Monot; David Rancourt; Sébastien Poncet (Water Resources and Industry)
Reducing the overall water and energy consumptions in deep mines is a necessity in moving toward a more sustainable mining industry. Underground water treatment is a key requirement to achieve this goal. This study numerically investigates the dynamics of a continuous decantation process as a technique to recycle and reuse wastewater in deep mines without pumping it to the surface. A three-dimensional mathematical model that considers the conservation of mass and momentum has been derived, validated, and implemented to simulate the turbulent two-phase flow inside a decantation tank. The validation is achieved by comparing the numerical simulations to experimental data from the literature for two reference cases: (i) turbulent slurry flows (water and glass particles) in a horizontal pipe; (ii) turbulent swirling flow of limestone ore - water in a hydrocyclone. The framework of the validated model has been extended to examine the effect of various design parameters on the efficiency of a full-scale conical-shaped decantation tank (diameter of 1 [m] and total height of 0.97 [m]). The inlet values of flowrate and particle volume concentration are fixed to 50 [GPM] and 4.5 [%], respectively. The diameter and density of the solid particles are equal to 150 [μm] and 1.15, respectively. The results compare the efficiency of 20 different designs of the decantation tank (with/without inner cylinder, scrapers, feedwell, …) in terms of the overflow water quality. The results indicate that the efficiency of the decantation tank increases with inner surface area at fixed volume. Also the plain decanter with scrapers exhibits the highest efficiency, whereas the design with the center extract performs the worst.